Status update control based on reinforcement learning in energy harvesting sensor networks - Han, Zhihui; Gong, Jie (Frontiers in Communications and Networks, 2022)
With the development of the Internet of Things, more and more sensors are deployed to monitor the environmental status. To reduce deployment costs, a large number of sensors need to be deployed without a stable grid power supply. Therefore, on the one hand, the wireless sensors need to save as much energy as possible to extend their lifetime. On the other hand, they need to sense and transmit timely and accurate information for real-time monitoring. In this study, based on the spatiotemporal correlation of the environmental status monitored by the sensors, status information estimation is considered to effectively reduce the information collection frequency of the sensors, thereby reducing the energy cost. Under an ideal communication model with unlimited and perfect channels, a status update scheduling mechanism based on a Q-learning algorithm is proposed. With a nonideal channel model, a status update scheduling mechanism based on deep reinforcement learning is proposed. In this scenario, all sensors share a limited number of channels, and channel fading is considered. A finite state Markov chain is adopted to model the channel state transition process. The simulation results based on a real dataset show that compared with several baseline methods, the proposed mechanisms can well balance the energy cost and information errors and significantly reduce the update frequency while ensuring information accuracy.